A Bayesian modeling framework for crash severity effects of active traffic management systems. (September 2020) - Khattak, Zulqarnain H.; Fontaine, Michael D.
Highlights: Crash Severity effects of Active Traffic Management (ATM) systems were assessed. A Bayesian modeling framework for mixed logit models with random parameters was proposed. Model results revealed a reduction of 12.4 % and 15.9 % for ATM with and without hard shoulder running. The models were observed to be temporally transferable. Abstract: Transportation agencies utilize Active traffic management (ATM) systems to dynamically manage recurrent and non-recurrent congestion based on real-time conditions. While these systems have been shown to have some safety benefits, their impact on injury severity outcomes is currently uncertain. This paper used full Bayesian mixed logit models to quantify the impact that ATM deployment had on crash severities. The estimation results revealed lower severities with ATM deployment. Marginal effects for ATM deployments that featured hard shoulder running (HSR) revealed lower likelihoods for severe and moderate injury crashes of 15.9 % and for minor injury crashes of 10.1 %. The likelihood of severe and moderate injury crashes and minor injury crashes reduced by 12.4 % and 8.33 % with ATM without HSR. The models were observed to be temporally transferable and had forecast error of 0.301 and 0.304 for the two models, revealing better performance with validation data. These results have implications for improving freeway crash risk at critical locations.